Off the clock : feel less busy while getting more done - Vanderkam, Laura (Portfolio/Penguin, 2018)
"In order to get more done, we must first feel like we have all the time in the world. Think about it: why haven't you trained for that 5K or read War and Peace? Probably because you feel beaten down by all the time you don't seem to have ... In this book, Vanderkam reveals the seven counter-intuitive principles the most time-free people have adopted. She teaches mindset shifts to help you feel calm on the busiest days and tools to help you get more done without feeling overwhelmed ... The strategies in this book can help if your life feels out of control, but they can also help if you want to take your career, your relationships, and your personal happiness to the next level. Vanderkam has packed this book with insights from busy yet relaxed professionals, including "time makeovers" of people who are learning how to use these tools."--Inside dust jacket.